2016
DOI: 10.1371/journal.pone.0163855
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microRNAs with Dysregulated Expression in Status Epilepticus Induced Epileptogenesis

Abstract: The involvement of miRNA in mesial temporal lobe epilepsy (MTLE) pathogenesis has increasingly become a focus of epigenetic studies. Despite advances, the number of known miRNAs with a consistent expression response during epileptogenesis is still small. Addressing this situation requires additional miRNA profiling studies coupled to detailed individual expression analyses. Here, we perform a miRNA microarray analysis of the hippocampus of Wistar rats 24 hours after intra-hippocampal pilocarpine-induced Status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…Brain tissue collected after death is typically used for comparison in case-control gene expression studies. Indeed, most studies are based on differences in gene expression between biopsies from MTLE patients and autopsy samples from non-epileptic individuals [ 21 , 22 ]. However, human postmortem tissue shows a high degree of biological variance [ 23 , 24 ] which may influence the results obtained by quantitative gene expression analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Brain tissue collected after death is typically used for comparison in case-control gene expression studies. Indeed, most studies are based on differences in gene expression between biopsies from MTLE patients and autopsy samples from non-epileptic individuals [ 21 , 22 ]. However, human postmortem tissue shows a high degree of biological variance [ 23 , 24 ] which may influence the results obtained by quantitative gene expression analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, upregulation of genes regulating synaptic physiology and transcription, homeostasis and metabolism and, cell excitability and morphogenesis occur at immediate, early, and delayed timepoints. In addition, related studies have demonstrated changes in expression of microRNAs related to epileptogenesis, including miRNA-124 and mi-RNA-128 following SE (80,81). Selective RNA editing post-transcription is yet another potential source of proteomic diversity in preclinical models of SE, and merits further investigation as a modulator of protein levels that may be less closely tethered to gene expression (82).…”
Section: Status Epilepticusmentioning
confidence: 99%
“…Araujo et al ( 2016 ) performed a miRNA microarray of the hippocampi of Wistar rats 24 h after intra-hippocampal pilocarpine-induced SE. A total of 73 miRNAs were found to be significantly dysregulated, of which 36 were up-regulated and 37 were down-regulated.…”
Section: Microrna and Epilepsymentioning
confidence: 99%